2020
DOI: 10.1016/j.jiac.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Development of the predicted and standardized carbapenem usage metric: Analysis of the Japanese Diagnosis Procedure Combination payment system data

Abstract: This study aimed to develop a metric for standardized and predicted carbapenem consumption using the Diagnosis Procedure Combination payment system database and patients' characteristics. Based on Diagnosis Procedure Combination data analysis, the developed metric will provide useful benchmarks that stewardship programs can use to help drive improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Detecting the specific associated factors in carbapenem consumption would be difficult, considering the similar medical functions and inpatient backgrounds in these hospitals. Meanwhile, respiratory diseases (MDC4) and hematologic diseases (MDC13) were significantly associated with the increment of carbapenem consumption in community hospitals consistent with the previous study [ 32 ]. Rhodes et al revealed the predictors of carbapenem consumption across North American hospitals [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Detecting the specific associated factors in carbapenem consumption would be difficult, considering the similar medical functions and inpatient backgrounds in these hospitals. Meanwhile, respiratory diseases (MDC4) and hematologic diseases (MDC13) were significantly associated with the increment of carbapenem consumption in community hospitals consistent with the previous study [ 32 ]. Rhodes et al revealed the predictors of carbapenem consumption across North American hospitals [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our previous DPC database analysis revealed that various MDCs were significantly associated with an increment in carbapenem consumption [ 32 ]. The stratification result by facility type in this study revealed a few associated factors in university hospitals and university hospital-equivalent community hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, antibiotic use metrics should evaluate antimicrobial use appropriateness or standardization [ 28 , 29 , 30 ]. The standardized antimicrobial administration ratio (SAAR), which was risk-adjusted for hospital-level and unit-level factors, has been implemented as a standardized benchmark of antibiotic use in the United States, although conventional metrics could not be quantitatively evaluated for appropriateness [ 28 ].…”
Section: Discussionmentioning
confidence: 99%